Legal Protection Of The Employment Relationship Created By The Company Employers With Outsourcing Companies (Outsourcing) According To Government Regulation In Lieu Of Law Number 2 Of 2022 About Job Creation In Medan City - Pramono, Rahman; Sahputra, Rilawadi; Kusbianto, Kusbianto (Universitas Dharmawangsa, 2024)
The problem raised in this paper is how the working relationship is made with the form of outsourcing (outsourcing) according to Perppu No. 2 of 2022 on job creation in Medan City, rights and obligations of outsourcing companies based on Perppu No. 2 of 2022 concerning job creation in Medan City, supervision by the Manpower office and sanctions for outsourcing companies that do not implement statutory provisions against workers. The method used in the discussion of the formulation of the problem is normative and empirical juridical law research by examining and analyzing using primary data and secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The working relationship between the outsourcing company and the workers/laborers employed is based on PKWT or PKWTT. This means that outsourced workers are linked to employment agreements made with employers based on provisions regarding PKWT or PKWTT. Rights and obligations describe a legal relationship between workers and the company, where both parties are equally bound by a mutually agreed labor agreement. Supervision of the implementation of this regulation is carried out by the Labor Inspectorate known as the Department of Labor. In addition, the Manpower office can also impose administrative sanctions for violations committed by outsourcing companies.